A remote surface loop modulates core structure and cold activity in phosphopantetheine adenylyltransferase - Yewon Nam; Jisub Hwang; Bogeun Kim; Jun Hyuck Lee; Hackwon Do (PLoS ONE, 2026)
Phosphopantetheine adenylyltransferase (PPAT), a key enzyme in the universal Coenzyme A biosynthetic pathway, is essential for cellular metabolism. However, the adaptive mechanisms of PPAT in psychrophilic (cold-adapted) organisms remain poorly understood. Here, we characterize PPAT from the psychrophilic methanotroph Methylocapsa palsarum ( Mpa PPAT). Sequence analysis identified a unique five-amino-acid insertion (SCRLS) within a surface-exposed loop, a feature conserved among psychrophilic homologues. To investigate its function, we determined the crystal structures of wild-type (WT) Mpa PPAT and a loop-deletion mutant ( Mpa PPAT(Δ67–71)) and performed comparative biochemical analyses. Structurally, Mpa PPAT forms a dimer-of-trimers hexamer. Biochemically, WT Mpa PPAT maintains high catalytic activity at low temperatures (10–20 °C), whereas the Mpa PPAT(Δ67–71) mutant exhibits impaired cold activity. The mutant structure reveals that the deletion of the distant surface loop induces a long-range allosteric change, resulting in a dual impairment: 1) a stabilization and rigidification (“clamping”) of the central α-helix 4 (H4) at the hexameric core interface, and 2) a dramatic shift in the central pore’s electrostatic potential from positive (WT) to negative (mutant). Our findings reveal that the SCRLS insertion is a critical allosteric modulator that provides a sophisticated dual mechanism for enzymatic cold adaptation. It maintains the conformational flexibility of the hexameric core, preventing the “clamping” effect, and simultaneously ensures a positively charged central channel to electrostatically steer negatively charged substrates (ATP and phosphopantetheine) into the active site, thereby overcoming the kinetic challenges of a low-temperature environment.